Characteristics of nitrogen and phosphorus contents in soil and water in an agricultural catchment of the three Gorges reservoir area - Chen, Chenglong; Deng, Hua; Xin, Guixin; Zhou, Youwen (Frontiers in Environmental Science, 2024)
To explore the impact of different land use modes on the contents of nitrogen and phosphorus in soil and water in the agricultural basin of the Three Gorges Reservoir, the differences in the nitrogen and phosphorus contents in soil and shallow groundwater under different land use modes were studied by using sample data collected in the field. The typical agricultural small watershed at the heart of the reservoir area was selected as the research object. The differences in the nitrogen and phosphorus loss concentrations during the rainfall process and in the daily surface runoff of the two subcatchments with different land use compositions and spatial layouts were compared. The results show that under the five land use modes, the average total nitrogen (TN) content of the paddy soil (1.51 g/kg) was the highest and was significantly higher than that of the other four land use modes (P<0.05); the average nitrate nitrogen (NO3 --N) content of the terraced soil in dry land (30.05 mg/kg) was the highest, and the dispersion degree was the greatest; and the total phosphorus (TP) content of the three types of sloping farmland was higher than that of terraced farmland, among which the total phosphorus content of the dryland sloping farmland (1.37 g/kg) was the highest and was significantly greater than that of the other types (P<0.05); moreover, the available phosphorus (AP) content in the soil of the closely planted mulberry garden was the highest, with an average of 36.85 mg/kg. Under the different land use modes, the concentrations of TN and NO3 --N in the shallow groundwater varied greatly, while there were no obvious differences in the TP concentrations. Influenced by fertilization, the concentrations of TN and NO3 --N in the shallow groundwater clearly increased after fertilization in spring and autumn. The concentration of TP increased slightly, and the concentration was the highest when the rainfall was concentrated in summer. A comparison of the two subcatchments revealed that the interplanted mulberry and paddy fields at the bottom of the basin effectively reduced TN and TP outputs of surface runoff in the subcatchment.